Genderisasi Mushaf Al-Qur’an: Studi Living Qur’an terhadap Desain Mushaf Wanita Muslimah - Mila, Kamilatus Sholehah; Rozi El Umam; Abd. Rahman (Jurnal Studi Qur'an dan Tafsir, 2024)
Related to the genderization of the Qur'an, this Qur'an is a Qur'an that has a more attractive appearance and is accompanied by a translation. Publishers do not hesitate to offer the advantages of their products compared to similar products from other publishers. They compete to hone their creativity, both in terms of cover, content, and completeness of additional text. Readers are increasingly spoiled with various sweet offers offered by publishers. This study intends to reveal two things: First, How are the visual models of genderization of the Qur'anic manuscripts. Second, What are the implications of using visual genderization of the Qur'anic manuscripts for women. This formulation, in addition to finding out how the visual models of genderization of the Qur'anic manuscripts are, is also to find out the implications of their use for women. This study is a literature review, which is based on primary data, in the form of manuscripts specifically for women and primary sources in the form of books related to this. This study concluded: First, the special Qur'an for women has many designs that can attract a woman to study it, in addition to being designed with a beautiful cover, the special Qur'an for women is also equipped with discussions on the laws of Islamic jurisprudence for women, in order to improve and add to the knowledge that they do not yet know. Second, the special Qur'an for women can affect a person's psychology and emotions, which are caused by color to humans in all aspects of life. In color therapy, color is often associated with a person's emotions. Color can also affect a person's mental or physical state. For example, several studies have shown that the color red often triggers an increase in heart rate which will lead to an increase in adrenaline pumped into the bloodstream.